A systematic review of incentives in blood donation. Issue 1 (6th November 2017) - Chell, Kathleen; Davison, Tanya E.; Masser, Barbara; Jensen, Kyle
Abstract : BACKGROUND: Incentives are often used to enhance the effectiveness of recruitment and retention campaigns targeting blood donors. However, the degree to which incentives succeed in attracting and facilitating repeat donation is unclear. A systematic literature review, following PRISMA guidelines, investigated the existing empirical evidence regarding the use of monetary and nonmonetary incentives within blood donation. STUDY DESIGN AND METHODS: A comprehensive search of relevant databases identified a total of 71 papers for inclusion in the review for defining and operationalizing incentives (Objective 1), of which nine papers empirically investigated attitudes toward incentives (Objective 2), 31 papers investigated the impact on blood donation behavior (Objective 3), and eight papers investigated the impact on blood safety (Objective 4). RESULTS: Overall, research into the use of incentives in blood donation is limited, characterized by comparatively few studies, predominantly focused on whole blood donors, that are confounded by current operating context (paid or voluntary). No incentive has been identified that all segments of the nondonor and donor panel report positive attitudes toward, that has a positive impact on behavior, and that has no negative impact on blood safety. Certain incentives (i.e., discounts, tickets, gifts, and paid time off work) have the strongest evidence base for potential inclusion within voluntary nonremunerated (VNR) donation systems. CONCLUSION: Due to the limited nature of the existing literature (particularly for apheresis donors) and inconsistencies observed within the results, additional research investigating the likely impact of introducing (or removing) monetary or nonmonetary incentives in VNR donor recruitment or retention is essential.